Manfaat Perkawinan Masyarakat Bugis dalam Perspektif Maqasid al-Syariah: : Mewujudkan Kemaslahatan - bayu, Yunus (Tamadduna: Jurnal Peradaban, 2025)
This qualitative study analyzed the implementation of Bugis community marriage practices in Malangke and found them to be in accordance with maqāṣid al-sharīʿah. Primary data was collected from traditional, religious, and community leaders. The research revealed that the cultural Islamization within Bugis marriage customs ensures their alignment with Islamic principles. This integration highlights the inherent benefits (maṣlaḥah) for both spouses within the cultural framework. Consequently, this marriage culture aligns with the concept of al-ʿādah aṣ-ṣaḥīḥah or al-ʿurf aṣ-ṣaḥīḥ (sound customs), making it a valid basis for legal considerations. Specific practices such as Mappasikarawa or Mappasiluka (initial contact) resonate with the Prophet Muhammad's (peace be upon him) guidance on marital blessings. Furthermore, rituals like Mappassau Botting and Cemme Passili (groom caring for and bathing the bride) align with the maqāṣid al-sharīʿah principle of lineage (nasl). The symbolic messages embedded within Bugis traditional marriages consistently reflect the community's values and the integration of maqāṣid al-sharīʿah, ultimately aiming to achieve good and prevent harm (maṣlaḥah).